Question #b9291

1 Answer
Jan 17, 2018

x = -2

Explanation:

Solving this is reasonably easy when you observe 1/e^2 is equivalent to e^-2 using exponent laws or more specifically the idea of 1/x^c = x^-c.

Then, one should understand the relation of ln to e. In layman's terms, you can think of ln and e "cancelling" each other. One should also understand that you can bring down exponents in a natural log or any log to the "base".

In math, you can say:

ln(e^-2) = -2ln(e), and that ln(e) = 1. Therefore, from this, we can say that -2 = x.